Assessment of coexisting psychosis and substance misuse: complexities, challenges and causality. (January 2021) - Nathan, Rajan; Lewis, Emily
SUMMARY: Substance misuse worsens the prognosis for people suffering psychosis and places them at risk of being denied appropriate mental health service interventions. To increase the chances of its success, the plan of management for patients with coexisting psychosis and substance misuse should be based on a valid formulation of their problems, which in turn is dependent on the clinician having (a) a thorough understanding of the bidirectional and changing ways that substance use and mental illness symptoms can interact, (b) an awareness of their own biased implicit assumptions about causality in explaining these interactions and (c) a framework for assessment and formulation. This article addresses these three areas with reference to the evidence base and to clinical experience in a way that guides mental health clinicians in the assessment of patients with coexisting psychosis and substance misuse.